Uniformity of large-area bilayer graphene grown by chemical vapor deposition. (9th September 2015) - Sheng, Yuewen; Rong, Youmin; He, Zhengyu; Fan, Ye; Warner, Jamie H
Abstract: Graphene grown by chemical vapor deposition (CVD) on copper foils is a viable method for large area films for transparent conducting electrode (TCE) applications. We examine the spatial uniformity of large area films on the centimeter scale when transferred onto both Si substrates with 300 nm oxide and flexible transparent polyethylene terephthalate substrates. A difference in the quality of graphene, as measured by the sheet resistance and transparency, is found for the areas at the edges of large sheets that depends on the supporting boat used for the CVD growth. Bilayer graphene is grown with uniform properties on the centimeter scale when a flat support is used for CVD growth. The flat support provides consistent delivery of precursor to the copper catalyst for graphene growth. These results provide important insights into the upscaling of CVD methods for growing high quality graphene and its transfer onto flexible substrates for potential applications as a TCE.